Kinematic Behavior of Al2024 T3 Aluminium Plate Subjected to Impact of 7.62mm Bullet - Ibrahim, Mohd Norihan; Hamdani, Mohd Qayyum (Research Progress in Mechanical and Manufacturing Engineering, 2020)
This study is concern about perforation process of single layer advanced high strength aluminum plate subjected to impact projectile motion. Numerical study had been carried out by using simulation from the ANSYS software to obtain the failure mode and perforation of the single layer Aluminum plate. ANSYS explicit finite element method was used to perform the simulation on the kinematics motion of bullet 7.62mm towards Al2024 T3 target plate at various range of velocity impact. The main focus of this research is concern about the dynamic behaviors response of bullet 7.62mm towards AL 2024-T3 target plate at low, medium and high velocity impact. Observation was focused along the simulation process and detailed investigation has been carried out on the deformation and perforation of the single layer Al2024 T3 target plate. From the result obtained, the bullet shape was effectively penetrating target plate at various impact velocity and the failure mode and contour were observed clearly after perforation due to penetration.